Decreased Platelet Number and Function and Increased Fibrinolysis Contribute to Postoperative Bleeding in Cardiopulmonary Bypass Patients - Holloway, D Scott; Summaria, Louis; Sandesara, Jyoti; Paul Vagher, J; Alexander, John C; Caprini, Joseph A (Thrombosis and Haemostasis, 1988)
We simultaneously evaluated platelet and fibrinolytic parameters to assess their individual and combined contributions to postoperative blood loss in cardiopulmonary (CP) bypass patients. Platelet count, platelet aggregability, hematocrit, plasminogen (PLG) concentration, alpha2-antiplasmin (AP) concentration, free protease activity (fPA), and antithrombin-III (AT-III) were measured in nine patients undergoing surgery using cardiopulmonary bypass. Chest tube drainage was used as the measure of postoperative blood loss. Hematocrit, platelet count, PT .G , AP and AT-TTT all decreased during CP bypass, with PLG and AT-III decreasing much more than dilution. During CP bypass, platelet aggregability to A DP did not change significantly from pre-bypass, but aggregability to arachidonic acid (AA) decreased significantly. Following protamine administration there was a large increase (83%) in fPA, the platelet count showed a further drop (from 61 % to 50% of pre-bypass levels) . and platelet aggregability decreased significantly (from 95% to 34% of prebypass levels for ADP, and from 55% to 11.9% for A A). Chest tube drainage during the first four postoperative hours correlated positively (p <0.05) with the combination of increase in free protease activity and decrease in platelet count. The total chest tube drainage correlated significantly with the combination of decrease in platelet count and the decrease in platelet aggregability. These combinations of changes correlated significantly with postoperative blood loss whereas the individual changes did not. These data indicate that during the early postoperative period the increased fibrinolytic activity and the decreased platelet count together contribute toward postoperative blood loss in CP bypass patients, and that during the entire first 24 hour period postoperatively the decreased platelet number and decreased platelet function are important contributors to blood loss.
Keywords: Blood platelets; Fibrinolysis; Bleeding; Cardiopulmonary bypass